2013
DOI: 10.1345/aph.1r486
|View full text |Cite
|
Sign up to set email alerts
|

Successful Clinical Use of Daptomycin-Impregnated Bone Cement in Two-Stage Revision Hip Surgery for Prosthetic Joint Infection

Abstract: Daptomycin impregnation of PMMA bone cement may be an option in cases in which patient or pathogen factors preclude use of routinely incorporated agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…In clinical trials, daptomycin was found to be equal with standard antibiotics in severe skin infections, bacteremia, and endocarditis caused by Gram-positive bacteria [23]. A case report documented a successful treatment of a recurrent prosthetic hip infection in a 70-year-old female with a past history of MRSA infection by using two-stage revision surgery with PMMA impregnated with daptomycin and gentamicin [24]. …”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials, daptomycin was found to be equal with standard antibiotics in severe skin infections, bacteremia, and endocarditis caused by Gram-positive bacteria [23]. A case report documented a successful treatment of a recurrent prosthetic hip infection in a 70-year-old female with a past history of MRSA infection by using two-stage revision surgery with PMMA impregnated with daptomycin and gentamicin [24]. …”
Section: Discussionmentioning
confidence: 99%
“…The actual dosage of daptomycin added in the bone cement as a spacer to treat PJI is unclear. Cortes et al reported the first case report of use of daptomycin 10 g and gentamicin 10 g in the bone cement (each agent at 5 % w/w) in two-stage revision hip surgery for prosthetic joint infection [ 17 ]. In an international consensus meeting on periprosthetic joint infection, 2 g daptomycin (5 % w/w) was recommended in spacers [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies also showed that daptomycin could be locally delivered from PMMA bone cement without impairing cement strength [ 15 , 16 ]. Only one clinical report showed combined use of daptomycin in bone cement and intravenously to treat chronic PJI in a 2-stage surgery [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, daptomycin appears to maintain bactericidal activity against stationary‐phase pathogens that may be embedded in biofilms associated with PJI . As is the case with many AIBC preparations, the optimal daptomycin dose has not been defined, and published clinical experience is limited to a total of 23 patients to date . The safety and resistance potential of daptomycin‐impregnated cements is largely unknown at this time.…”
Section: Antimicrobial Selectionmentioning
confidence: 99%
“…61 As is the case with many AIBC preparations, the optimal daptomycin dose has not been defined, and published clinical experience is limited to a total of 23 patients to date. 43,51 The safety and resistance potential of daptomycin-impregnated cements is largely unknown at this time. Given its status as the first-in-class lipopeptide, low resistance rates observed, and favorable safety profile when used systemically, stewardship of daptomycin cement use is imperative to preserve long-term effectiveness.…”
Section: Lipopeptidesmentioning
confidence: 99%